Climate Change-Related Salinity Fluctuations and Warming Induce Physiological Stress and Cellular Alterations in an Antarctic Intertidal Brown Alga - Morales, Francisca; Munoz, Pamela T.; Undabarrena, Agustina; Celis-Pla, Paula S. M.; Ramila, Consuelo; Aguilar-Munoz, Polette; Molina, Veronica; Navarro Martinez, Nelso Patricio; Saez, Claudio A.; Lavergne, Celine; Camara, Beatriz; Tessini, Catherine; et al. (My University, 2025)
Antarctica is experiencing one of the fastest warming rates globally, profoundly impacting seawater temperature and salinity, with direct consequences for marine life. The present study examined the combined effects of salinity fluctuations at 20, 33 (control salinity), and 41 psu, and temperatures of 2 degrees C (control temperature) and 8 degrees C (thermal stress) for 3 days, on the health and physiology of the Antarctic intertidal macroalga Adenocystis utricularis. Photosynthetic activity, photoinhibition, and photoprotective processes were assessed alongside biomarkers of oxidative stress/damage (total ROS, lipid peroxidation, and protein carbonylation) and antioxidant/osmotic response (ascorbate, free amino acids, and proline). The results showed that maximum quantum yield (Fv/Fm) remained stable under both salinity and thermal stress. However, productivity (ETRmax), the photoprotection index (NPQmax), and irradiance saturation (EkETR) were significantly decreased at 8 degrees C, remaining constant under salinity fluctuations. At 2 degrees C, oxidative stress and damage were significantly higher under hypo- and hypersalinity conditions. However, at 8 degrees C, oxidative stress indicators decreased, accompanied by increased ascorbate levels in both hypo- (20 psu) and hypersalinity (41 psu) treatments compared to the control salinity. While warming temperatures negatively altered the oxidative response of A. utricularis at a 33 psu, we report here an interactive effect between salinity and temperature, leading to an altered stress response to salinity fluctuations under thermal stress. This study provides key information to better understand the adaptation of Antarctic intertidal macroalgae to multifactor climate change consequences.
Keywords: climate change; antarctica; photosynthesis; macroalgae; biomarkers; thermal stress; salinity stress